1997
DOI: 10.1097/00002030-199708000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Two parallel routes of the complement-mediated antibody-dependent enhancement of HIV-1 infection

Abstract: These novel findings indicate that besides the well-known facilitation of entry of HIV-1 by the interaction between virus-bound C3 fragments and CR2 present on the target cells, fixation of C1q to intact virions also results in an enhanced productive HIV-1 infection in the MT-4 cell cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Another mechanism could involve complement-mediated, antibody-dependent enhancement of HIV-1 infection. HIV-IgA immune complexes could be coated by C3 fragments; the interaction between virusbound C3 and CR2 (CD21) has been reported elsewhere to enhance HIV-1 infection [24].…”
Section: Discussionmentioning
confidence: 85%
“…Another mechanism could involve complement-mediated, antibody-dependent enhancement of HIV-1 infection. HIV-IgA immune complexes could be coated by C3 fragments; the interaction between virusbound C3 and CR2 (CD21) has been reported elsewhere to enhance HIV-1 infection [24].…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, viruses from various families elicit antibodies that enhance infectivity through the binding of virus-antibody complexes to cellular Fc receptors (expressed in, e.g., monocytes/macrophages) via the Fc portion of the antibodies (24,44,49). Fixation of the C3 or C1q complement proteins, activated by virus-antibody complexes, can also facilitate virus entry, as shown for the antibody-dependent, complement-mediated enhancement of infection of human immunodeficiency virus (19,46,53) and Ebola virus (54). Finally, in vitro enhancement of human immunodeficiency virus infection via an antibody-independent mechanism that involves receptors of the classical and alternative complement pathways has been reported (5,21).…”
Section: Discussionmentioning
confidence: 99%
“…The resultant complex, consisting of the virus, antibodies and C1q, binds C1q receptors (C1qR) at the cell surface, promoting either binding of the virus to Ebola virus-specific receptors or endocytosis of the target cells by intracellular signalling via C1qR [69,70]. Prohaszka et al [71] also suggested that C1q-mediated ADE might underlie HIV infection, although the mechanism of enhancement remains elusive, since C1q directly binds to HIV gp41 [69,72].…”
Section: Ebola Virusmentioning
confidence: 99%